Business English as a lingua franca - a cross-cultural perspective of teaching English for business purposes - Gajšt, Nataša (ELOPE (Ljubljana), 2014)
In our era of globalisation, English is at the top of the languages used in international business. A vast majority of business communication in English is carried out by non-native speakers of English. In a cross-cultural exchange of information, the sender and the recipient come from different cultural backgrounds. The patterns of communication vary across the globe and non-native speakers tend to apply their native language patterns when communicating in English. This paper thus focuses on the concept of spoken communication and dimensions of culture and how they are reflected in communication patterns in different business situations. It also addresses the teaching of Business English as a lingua franca and the role of Business English teachers in helping learners develop their communicative and intercultural competence in order to communicate effectively in a multicultural work environment.
Keywords: komunikacijski vzorci; komunikativna kompetenca; lingua franca; medkulturna kompetenca; medkulturna komunikacija; poslovna angleščina; Skupni evropski jezikovni okvir (SEJO)